2008
DOI: 10.1007/s00192-008-0695-7
|View full text |Cite
|
Sign up to set email alerts
|

The aetiology of prolapse

Abstract: Female pelvic organ prolapse is a common condition that is said to be multifactorial in aetiology. While a number of risk factors such as vaginal childbirth, obesity and ageing are commonly accepted, it is not clear as to how these risk factors affect the development of prolapse-that is, which pathophysiologic mechanisms are responsible for disease manifestation. Measures used in epidemiological studies, such as presentation for surgical treatment, are generally confounded by other conditions, and evidence is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 68 publications
1
54
0
1
Order By: Relevance
“…Furthermore, other factors, such as fascial fibre tearing, altered skeletal anatomy, reduced levator ani tone due to neuronal damage and levator ani avulsion following childbirth, may also contribute to prolapse development. 2,70,71 Levator avulsion defect is the traumatic muscle detachment of the puborectalis muscle from its insertion on the inferior pubic rami. This injury occurs in up to 36% of women 72 and has been shown to be associated with prolapse, particularly in the anterior and central compartment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, other factors, such as fascial fibre tearing, altered skeletal anatomy, reduced levator ani tone due to neuronal damage and levator ani avulsion following childbirth, may also contribute to prolapse development. 2,70,71 Levator avulsion defect is the traumatic muscle detachment of the puborectalis muscle from its insertion on the inferior pubic rami. This injury occurs in up to 36% of women 72 and has been shown to be associated with prolapse, particularly in the anterior and central compartment.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the traditional risk factors such as age, parity, vaginal childbirth and increased intra-abdominal pressure (ie obesity, chronic cough and constipation) 2 , the concept of a genetic tendency towards prolapse is becoming more apparent. For example, women with a positive family history of POP are more likely to develop prolapse compared to women with no family history (OR 2.58, 95% CI 2.12-3.15).…”
Section: Introductionmentioning
confidence: 99%
“…If hiatal ballooning is associated with an increased risk of RI, would a reduction in hiatal area ameliorate or cure RI? This constitutes an area for future research, especially as such work would also have widespread repercussions in the treatment of vaginal prolapse [30].…”
Section: Discussionmentioning
confidence: 99%
“…After Logistic Regression presence of at least one vaginal delivery, fetal macrosomia and positive family history for dystocia have reported as independent risk factors in POP [20]. Although several studies have confirmed the effect of increasing age on the incidence and severity of POP [9,[21][22][23][24], in a case study reported the third-degree uterine prolapse in 11-month-old infant [25].…”
Section: Resultsmentioning
confidence: 99%